Recent Progress in Flexible Microstructural Pressure Sensors toward Human–Machine Interaction and Healthcare Applications. Issue 3 (18th January 2021) - He, Faliang; You, Xingyan; Wang, Weiguo; Bai, Tian; Xue, Gaofei; Ye, Meidan
Abstract: With the rapid growth of artificial intelligence, wearable electronic devices have caught intensive research interest recently. Flexible sensors, as the significant part of them, have become the focus of research. Particularly, flexible microstructural pressure sensors (FMPSs) have attracted extensive attention because of their controllable shape, small size, and high sensitivity. Microstructures are of great significance to improve the sensitivity and response time of FMPSs. The FMPSs present great application prospects in medical health, human–machine interaction, electronic products, and so on. In this review, a series of microstructures (e.g., wave, pillar, and pyramid shapes) which have been elaborately designed to effectively enhance the sensing performance of FMPSs are introduced in detail. Various fabrication strategies of these FMPSs are comprehensively summarized, including template (e.g., silica, anodic aluminum oxide, and bionic patterns), pre‐stressing, and magnetic field regulation methods. In addition, the materials (e.g., carbon, polymer, and piezoelectric materials) used to prepare FMPSs are also discussed. Moreover, the potential applications of FMPSs in human–machine interaction and healthcare fields are emphasized as well. Finally, the advantages and latest development of FMPSs are further highlighted, and the challenges and potential prospects of high‐performance FMPSs are outlined. Abstract : This review systematically summarizes the current development of flexible microstructural pressure sensors (FMPSs). A series of microstructures which have been elaborately designed to enhance the sensing performance of FMPSs are introduced in detail. The methods and materials for the fabrication of FMPSs and their applications in human–machine interaction and healthcare are also discussed.